ANALISIS HUKUM ULTRA PETITUM PARTIUM PADA PUTUSAN HAKIM DALAM PERKARA PEMUTUSAN HUBUNGAN KERJA DI PENGADILAN HUBUNGAN INDUSTRIAL PEKANBARU ( STUDI KASUS PUTUSAN NOMOR 23/G/PDT.SUS-PHI/2015/PN.PBR) - Sijabat, Sandro Imanuel; Ismi, Hayatul; ', Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
The Court decision as a product that became the first typographical arrangement of a court, must contain a comprehensive legal considerations and providing justice for the litigants. In the Industrial Relations Court verdict Pekanbaru No. 23/G/PDT.SUS-PHI/2015/PN.PBR, the judge had erred in giving consideration to the case of Termination of Employment. In consideration of judges did not notice any bad faith on the company that showed the Company do not want Jusman Zebua as a worker to return to work. In Article 178 paragraph (3) HIR and Article 189 Paragraph (2) RBg expressly stated that the judge in deciding a case should not be a decision beyond than what is sued, known as the principle of Ultra Petitum Partium. The application of this principle can be made along the verdict reflects justice. The judge in the verdict has been applying the principles of Ultra Petitum Partium with rehiring Jusman Zebua that has be terminated by the Company. But the decision to reinstate the suit does not fit the core framework so that the decision does not give it justice.The purpose of this thesis are: First to know the basic consideration of the judge at the Industrial Relations Court in the hearing and decide the case Termination No. 23/Pdt.Sus-PHI/2015/PN.PBR, second, to determine ultra partium petition at court judge's ruling Industrial relations No.23/Pdt.Sus-PHI/ 2015/PN.PBR in the case of Termination of Employment provide justice for workers / laborers.This research is a normative legal research or also called the doctrinal legal research. From the research problem there are two main things that concluded, first, the judge should give comprehensive consideration in accordance with the facts and with regard to the provisions of legislation in force so as not to cause harm to the litigants. Second, the adoption of the principle of Ultra Petitum Partium the judge's decision does not provide justice for workers/ laborers who have be terminated then the Industrial Relations Court Judges should be more careful in observing the core framework lawsuit sued by the plaintiffs in order to realize justice in the judge's decision.Keywords: Legal Analysis-Ultra Petitum Partium-Verdict Judge-Termination of Employment-The Industrial Relations Court